IMPROVING STUDENTS READING PROFICIENCY USING BIONIC METHOD (A CLASSROOM ACTION RESEARCH AT 10th GRADE STUDENTS) - Etika Ariyani (Bajang Institute, 2023)
The purpose of this study was to improve the students reading ability by using bionic method at 10th grade students. This research was a classroom action research (CAR) and it was conducted in two cycles. Each cycle consisted of four stages namely planning, acting, observing and reflecting. The subject of this research were 30 students. The data collection method of this study were test, observation, field notes and documentation. The result of this study showed that there was a significant improvement from first to second cycle. The average at first post test was 67 with the percentage of students successful achievement 63 % and the last cycle, the average score was 72 with the percentage of students successfulness 75 %. It means that the indicator of Minimum Mastery Criteria (MMC) has been achieved at least 70 % students were completed..This result indicated that using bionic method could improve students reading proficiency significantly at 10th students of Senior High School